THE EFFECT OF EXPERIENTIAL MARKETING AND PERCEIVED PRICE ON CUSTOMER LOYALTY: THE MEDIATING ROLE OF CUSTOMER SATISFACTION AND REVISIT INTENTION - Syamsul Bahri (CV. Radja Publika, 2025)
Indonesia is a beautiful archipelago, with its mountainous terrain making it a popular tourist destination. One such location is Lake Lut Tawar in Central Aceh Regency, ideal for camping. Companies must improve customer satisfaction and loyalty due to the intense competition in the Indonesian tourism industry, which attracts both domestic and international visitors. Customer loyalty is the dependent variable in this study, and customer satisfaction and revisit intention are the intervening variables. The independent variables examined in this study are experiential marketing and perceived price. The results show that experiential marketing has been shown to increase customer satisfaction; perceived price has been shown to increase customer satisfaction; experiential marketing has been shown to increase revisit intention; perceived price has been shown to increase revisit intention; experiential marketing has not been able to increase customer loyalty; perceived price has been shown to increase customer loyalty; customer satisfaction has been shown to increase customer loyalty; revisit intention has been shown to increase customer loyalty. In addition, customer satisfaction has a positive and significant effect on customer loyalty. This shows that when customer satisfaction increases, customer loyalty will increase; customer satisfaction cannot mediate the relationship between experiential marketing and customer loyalty. and finally, revisit intention partially mediates the relationship between perceived price and customer loyalty.